THE ROLE OF SOCIAL NETWORKS IN FACILITATING ACCESS TO CAPITAL AND RESOURCES FOR START-UP ENTREPRENEURS IN INDONESIA - Susantinah Wisnujati, Nugrahini; Junaidi, Ahmad; Ausat, Abu Muna Almaududi (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze the role of social networks in facilitating access to capital and resources for start-up entrepreneurs in Indonesia. As a literature review employing a qualitative approach, the research utilizes secondary data sourced from Google Scholar between 2003–2024, selecting 19 articles. Descriptive analysis explores how social networks, encompassing personal relationships, business communities, and digital platforms, assist start-up entrepreneurs in overcoming challenges related to accessing capital, knowledge, and collaboration opportunities. Findings indicate that social networks play a critical role in creating funding opportunities through interpersonal connections, leveraging crowdfunding platforms, and establishing strategic connections via business communities and social media. Relevant case studies highlight the success of start-up entrepreneurs in Indonesia who have utilized social networks to expand their businesses and overcome operational challenges. However, the study also finds that the effectiveness of social networks depends on digital literacy, relationship-building capabilities, and community support. Digital literacy training, strengthening business communities, and educating entrepreneurs on leveraging social networks should be prioritized to support the growth of start-up entrepreneurs in Indonesia.